P193 MECHANICAL COMPRESSION DEVICE (LUCAS®) IN THE CATHETERIZATION LABORATORY: RETROSPECTIVE ANALYSIS OF A SINGLE CENTER. (18th May 2022) - Dal Passo, B; Cardelli, L; Capecchi, A; Nobile, G; Canovi, L; Frascaro, F; Zanarelli, L; Piscitelli, L; Casella, G
Abstract: Background: The survival of IHCA and OHCA depends on the timeliness and the quality of cardiopulmonary resuscitation (CPR). During transport, in the Cath Lab or when resuscitation is extended, the availability of chest compression systems increases the quality of CPR and it is recommended in these specific situations by the AHA 2020 Guidelines. Methods: Retrospective analysis of patients who encountered cardiocirculatory arrest (CCA) in the Cath Lab or in ICU of the Maggiore Hospital managed with CPR and application of a chest compression device (LUCAS® 3) from 2020 to 2021. Results: The study population consisted of 21 patients, all undergoing invasive procedure (coronary angiography, angioplasty or aortic valvuloplasty) in peri–arrest: 17 patients (81%) with CCA during STEMI, 3 (14%) during NSTEMI and one patient during acute pulmonary edema caused by severe aortic stenosis. In 6 cases (29%) the onset rhythm of CCA was shockable, the others were pulseless electrical activities. Considering patients admitted with STEMI, 4 (24%) have OHCA and LUCAS® had been applied by 118 operators before entering the Cath Lab. In the other cases LUCAS® was placed in the Cath Lab, before or during the procedure; in all but two cases, the procedure was concluded. The resuscitation maneuvers involved, in addition to LUCAS®, the use of an external defibrillator, orotracheal intubation, administration of inotropes and, in 2 cases (10%) the intra–aortic balloon pump (IABP). The average time between CCA and application of LUCAS® was 14 minutes – the device was always positioned after at least 2 manual ECM cycles without restoring the circulation – and the average CPR duration was 73 minutes. Any complications related to the implantation of the device were observed. The survival at the end of the procedure in the Cath Lab was 24% and on discharge 14%. Conclusion: The use of chest compression devices during CCA allows a better management by medical personnel during long–term CPR and a completion of invasive procedure. Unfortunately, it doesn't substantially changes the survival of patients as reported by the literature.